Film

By dispersing unloaded composite catalyst particles in the electrolyte membrane and forming a single adherent membrane structure, the problem of hydrogen and oxygen mixing in the existing membrane under high pressure difference is solved, low hydrogen permeability and high ion conductivity are achieved, and operating costs are reduced and maintenance requirements.

CN119317736APending Publication Date: 2025-01-14JOHNSON MATTHEY HYDROGEN TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380044868.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-27
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The mixing of hydrogen and oxygen under high pressure difference causes safety problems, and the large thickness leads to increased electron and ion resistance, which makes maintenance costs high.

Method used

Electrolyte membranes with a thickness of less than or equal to 100 μm were developed, by dispersing unsupported composite catalyst particles in the membrane layer and forming a single adherent film structure, combining the composite catalyst to achieve low hydrogen permeability and high ion conductivity.

Benefits of technology

An excellent balance between low hydrogen permeability and high ion conductivity under high pressure difference is achieved, reducing the compression requirements and operating costs of hydrogen, while improving the stability and manufacturing efficiency of the membrane.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317736A_ABST
    Figure CN119317736A_ABST
Patent Text Reader

Abstract

An electrolyte membrane including a composite catalyst layer is provided. The membrane has a thickness of less than or equal to 100 [mu] m and is a single adhesive polymer membrane comprising a plurality of ion conducting polymer layers. The composite catalyst layer comprises particles of an unsupported composite catalyst dispersed in an ion conducting polymer, and the layer has a thickness in the range of from 5 [mu] m to 30 [mu] m and including 5 [mu] m and 30 [mu] m. Also provided are a catalyst coated film (CCM) incorporating the electrolyte membrane, and a method of manufacturing the electrolyte membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electrolyte membranes, and their use in electrochemical devices such as water electrolyzers, and includes catalyst coated membranes (CCMs) incorporating such membranes, and methods of making them. Background Art

[0002] The electrolysis of water can be performed in both alkaline and acidic electrolyte systems to produce high purity hydrogen and oxygen. Those electrolyzers that employ solid proton-conducting polymer electrolyte membranes or proton exchange membranes (PEMs) are referred to as proton exchange membrane water electrolyzers (PEMWEs). Those electrolyzers that utilize solid anion-conducting polymer electrolyte membranes or anion exchange membranes (AEMs) are referred to as anion exchange membrane water electrolyzers (AEMWEs).

[0003] Catalyst coated membranes (CCMs) may be employed in stacks of water electrolyzers. CCMs include an electrolyte membrane (such as a PEM or AEM) in which at least one of an anode catalyst layer and a cathode catalyst layer is coated on the face of the membrane. Typically, for PEMWEs, the cathode catalyst material includes platinum. Anode catalysts for PEMWEs typically include iridium or iridium oxide (IrOx) materials or oxides containing both iridium and ruthenium.

[0004] To form a water electrolyzer, additional layers are added on either side of the CCM to make an assembly, sometimes referred to as a membrane electrode assembly (MEA). These additional layers may include a porous transport layer (PTL) on the anode side of the CCM and a gas diffusion layer (GDL) on the cathode side. These layers may or may not be directly attached to the CCM. Other components may include bipolar plates and current collector plates. A stack of such components constitutes an electrolyzer system including power and control systems.

[0005] Electrolyte membranes such as PEMs and AEMs are also used in fuel cells. In a proton exchange membrane fuel cell (PEMFC), the membrane is proton conducting and transports protons generated at the anode across the membrane to the cathode where they combine with oxygen to form water.

[0006] It is desirable to reduce the thickness of membranes used in electrochemical devices such as water electrolyzers to minimize electronic and ionic resistance. However, it is also important to minimize any hydrogen permeation through the membrane to avoid mixing of hydrogen with oxygen and associated safety issues.

[0007] For water electrolyzers, it is beneficial to maintain low levels of hydrogen permeation even at high pressure differentials across the membrane. The use of high pressure during electrolyzer operation is advantageous because it reduces the degree of compression required for the hydrogen produced and reduces operating costs. This has led to the use of membranes with thicknesses exceeding 125 μm and often approaching 200 μm or more. Examples of membranes currently in use include Nafion TM N115 (thickness 125μm) or Nafion TM N117 (thickness 175 μm).

[0008] It is also important that the membrane remain stable during long-term electrochemical operation to minimize maintenance and replacement of expensive parts.

[0009] It is known to coat membrane components with a catalyst layer suitable for catalyzing the recombination reaction of molecular oxygen and hydrogen. For example, in WO2018 / 115821 (Johnson Matthey Fuel Cells Ltd) it is described that a Pt / C supported catalyst can be coated onto one surface of a membrane and the membrane laminated with other membrane layers to form a CCM component for a PEM water electrolyser.

[0010] It is also known to produce proton exchange membranes comprising supported composite catalysts. For example, in WO2020 / 148545 (Johnson Matthey Fuel Cells Ltd.) it is described that a catalyst comprising platinum nanoparticles on a graphene support can be introduced into the membrane.

[0011] There remains a need to further enhance and develop membranes for electrochemical applications, such as for water electrolysis applications, that are capable of operating efficiently at high pressure differentials across the membrane. Summary of the invention

[0012] The present inventors have surprisingly discovered that electrolyte membranes having a thickness of less than or equal to 100 μm can be produced with an excellent balance of low hydrogen permeation and high ionic conductivity. Such membranes can be produced by dispersing unsupported composite catalyst particles in a membrane layer having a controlled thickness and forming the membrane as a single coherent membrane without a lamination interface. Such membranes are able to incorporate composite catalysts while maintaining high ionic conductivity.

[0013] Thus, in a first aspect of the invention there is provided an electrolyte membrane, such as a proton exchange membrane, comprising a composite catalyst layer, the membrane having a thickness less than or equal to 100 μm, and wherein the composite catalyst layer meets the following requirements:

[0014] (i) the layer comprises particles of an unsupported composite catalyst dispersed in an ion-conducting polymer;

[0015] (ii) the layer has a thickness in the range of 5 μm to 30 μm inclusive and the electrolyte membrane is a single coherent polymer membrane comprising a plurality of ion-conducting polymer layers.

[0016] Such membranes are particularly suitable for use in water electrolysers.Providing the membrane as a single non-laminated component, rather than, for example, two or more membrane components laminated together, additionally provides large scale stability benefits and manufacturing process efficiencies.

[0017] The membrane of the first aspect has particular use as a component of a catalyst coated membrane (CCM). It has been found that such CCMs provide an excellent balance between membrane resistance and low hydrogen permeation during operation. Therefore, in a second aspect of the invention, there is provided a CCM for an electrochemical device, the CCM comprising a membrane according to the first aspect.

[0018] Suitably, the CCM is used in a water electrolyser, such as a PEM water electrolyser. In such cases, the CCM comprises a cathode catalyst layer for catalyzing the hydrogen evolution reaction and / or an anode catalyst layer for catalyzing the oxygen evolution reaction. Typically, the cathode catalyst layer comprises platinum and / or the anode catalyst layer comprises iridium.

[0019] The CCM may also be used in a fuel cell, such as a PEM fuel cell. In such a case, the CCM includes a cathode catalyst layer for catalyzing an oxygen reduction reaction and / or an anode catalyst layer for catalyzing an hydrogen oxidation reaction.

[0020] In a third aspect of the present invention, there is provided a water electrolyser or a fuel cell, the water electrolyser or the fuel cell comprising the membrane according to the first aspect or the catalyst coated membrane according to the second aspect.

[0021] The inventors have also advantageously found that an electrolyte membrane comprising a composite catalyst layer as described herein can be prepared by preparing an ink, preferably controlling the composite catalyst particle size distribution, and then using such ink to prepare a composite catalyst layer. Therefore, in a fourth aspect of the present invention, there is provided a method for manufacturing an electrolyte membrane according to the first aspect, the method comprising the following steps:

[0022] (i) forming an ink comprising particles of an unsupported composite catalyst and an ion-conducting polymer;

[0023] (ii) Producing a composite catalyst layer from the ink. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 A schematic diagram showing an example arrangement of the electrolyte membrane of the present invention.

[0025] Figure 2A schematic diagram showing an example arrangement of a catalyst coated membrane of the present invention.

[0026] Figure 3 A scanning electron microscopy (SEM) image of a film formed according to Example 1 is shown.

[0027] Figure 4 The results of hydrogen permeation tests of the films produced in Examples are shown.

[0028] Figure 5 The electrical test results of the 80 μm film produced in the examples are shown. DETAILED DESCRIPTION

[0029] The preferred and / or optional features of the present invention will now be described. Unless the context otherwise requires, any aspect of the present invention may be combined with any other aspect of the present invention. Unless the context otherwise requires, any preferred and / or optional features of any aspect may be combined with any aspect of the present invention individually or in combination.

[0030] The present invention provides electrolyte membranes. Preferably, the membrane is a proton exchange membrane (PEM), such as a PEM for a water electrolyzer. However, it will be appreciated by those skilled in the art that the composite catalyst layer as described herein will be useful for other types of electrolyte membranes, such as a proton exchange membrane for a fuel cell, and an anion exchange membrane for a water electrolyzer, a fuel cell or other applications.

[0031] The film has a thickness less than or equal to 100 μm. Preferably, the film has a thickness less than or equal to 95 μm, 90 μm or 85 μm. Preferably, the film has a thickness of at least 10 μm, such as at least 15 μm, at least 20 μm, at least 25 μm, at least 30 μm or at least 40 μm. It is further preferred that the film has a thickness in the range of 10 μm to 100 μm and including 10 μm and 100 μm, such as 15 μm to 100 μm, 20 μm to 100 μm, 30 μm to 100 μm, 30 μm to 90 μm or 40 μm to 90 μm.

[0032] The film thickness (and the thickness of the film's layers) can be measured by scanning electron microscopy (SEM). SEM analysis is performed on a cross section of the film and the film and / or layer thickness is measured at a plurality of (e.g., 10) points. Subsequently, the thickness value is determined by calculating the arithmetic mean of the measured values.

[0033] The membrane includes a composite catalyst layer. The so-called composite catalyst refers to a catalyst that catalyzes the reaction between hydrogen and oxygen to generate water. Therefore, the composite catalyst used in the composite catalyst layer of the present invention can be any catalyst that can catalyze the reaction between hydrogen and oxygen to form water, thereby reducing or preventing hydrogen or oxygen or both from permeating through the membrane. It will be appreciated by those skilled in the art that the membrane may include more than one composite catalyst layer, such as two or more composite catalyst layers. It is preferred that the membrane has a single composite catalyst layer.

[0034] Suitably, the composite catalyst is selected from one or more of platinum, palladium and their alloys or mixed oxides. Preferably, the composite catalyst is platinum or a platinum alloy, such as platinum alloyed with one or more other platinum group metals (i.e., the element group comprising platinum, palladium, iridium, rhodium, ruthenium and osmium) or platinum alloyed with cobalt. Particularly preferably, the particles of the unloaded composite catalyst are composed of platinum.

[0035] The composite catalyst is unloaded. The term "unloaded" will be readily understood by the skilled person. For example, it will be understood that the catalyst particles are not bound or fixed to a catalyst support (such as a carbon support) by physical or chemical bonds (e.g., by ionic or covalent bonds) or non-specific interactions (such as de Waal forces). It has been found that the use of an unloaded composite catalyst facilitates ink processing prior to film formation and provides increased film stability during electrochemical operation, thereby avoiding degradation pathways via corrosion of the catalyst support.

[0036] The composite catalyst layer is a membrane layer comprising particles of an unsupported composite catalyst dispersed in an ion-conducting polymer.

[0037] In the case where the membrane is used in a PEM electrochemical device, the ion-conducting polymer is suitably a proton-conducting polymer, and in particular a partially fluorinated sulfonic acid polymer or a fully fluorinated sulfonic acid polymer. Examples of suitable proton-conducting polymers include perfluorosulfonic acid (PFSA) polymers, such as perfluorosulfonic acid polymers available from 3M Corporation or Aquivion (RTM) ion-conducting polymers available from Solvay. It is preferred that the ion-conducting polymer is a PFSA polymer and has an equivalent mass (EW) of greater than 750 EW, greater than 760 EW, greater than 770 EW or greater than 790 EW. For example, it may be preferred that the ion-conducting polymer is a PFSA polymer having an equivalent mass in the range of 750 EW to 1200 EW, including 750 EW to 1200 EW, such as in the range of 770 EW to 1000 EW, including 770 EW to 1000 EW, or in the range of 800 EW to 900 EW, including 800 EW to 900 EW. It may be preferred that the equivalent mass of the ion-conducting polymer in the composite catalyst layer is greater than the equivalent mass of the ion-conducting polymer in any other layer of the membrane.

[0038] Dispersed in the ion-conducting polymer means herein that the particles of the unsupported composite catalyst are distributed throughout the composite catalyst layer, ie, they are not located in discrete layers or regions of the composite catalyst layer.

[0039] Preferably, the particles of the unloaded composite catalyst have a particle size distribution such that d90 is less than or equal to 3.0 μm. The use of particles having a d90 less than or equal to 3.0 μm provides improved mechanical stability in a film layer (such as a layer having a thickness of less than 30 μm) and provides benefits associated with ink processability and the use of the ink in a coating device. The term "d90" used with respect to the particle size distribution in the film refers to the number distribution of particle sizes (the particle size value at 90% in the cumulative number distribution, i.e., 90% of the total particles in the sample have a diameter less than this value). The d90 of the particles in the film can be determined by scanning electron microscopy (SEM), for example, by analyzing a cross section of the film by SEM, measuring the diameter of a particle group (e.g., 100) by image analysis based on the resulting image, and then calculating d90.

[0040] Preferably, d90 is less than or equal to 2.8 μm, 2.6 μm, 2.5 μm, 2.4 μm, 2.3 μm, 2.2 μm, 2.1 μm or 2.0 μm. Preferably, the particles of the unloaded composite catalyst have a particle size distribution such that d90 is greater than or equal to 1.0 μm, 1.5 μm, 1.7 μm or 1.9 μm. It may be further preferred that the particles of the unloaded composite catalyst have a particle size distribution such that d90 is in the range of 1.0 μm to 3.0 μm and includes 1.0 μm and 3.0 μm or in the range of 1.5 μm to 3.0 μm and includes 1.5 μm and 3.0 μm, such as 1.5 μm to 2.8 μm or 1.5 μm to 2.6 μm.

[0041] Typically, the particles of the unloaded composite catalyst have an average particle size greater than or equal to 0.1 μm. The average particle size can be determined by scanning electron microscopy (SEM), for example by analyzing the cross section of the film by SEM, and measuring the diameter of the observable particle group (e.g., 100) by image analysis based on the resulting image, and then calculating the average (mean) particle size. The use of particles greater than 0.1 μm provides advantages regarding efficient ink preparation, and their use has been shown to provide a significant reduction in hydrogen permeation.

[0042] Preferably, the average particle size is greater than or equal to 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm or 0.9 μm. Preferably, the particles of the unloaded composite catalyst have an average particle size less than or equal to 2.0 μm, 1.8 μm, 1.6 μm, 1.5 μm, 1.4 μm, 1.3 μm or 1.2 μm. Preferably, the particles of the unloaded composite catalyst have an average particle size in the range of 0.2 μm to 2.0 μm and including 0.2 μm and 2.0 μm, in the range of 0.5 μm to 2.0 μm and including 0.5 μm and 2.0 μm, such as 0.7 μm to 1.8 μm or 0.8 μm to 1.5 μm.

[0043] Preferably, the electrolyte membrane has a -2 Up to 50g / cm -2 , 5g / cm -2 Up to 40g / cm -2 , 5g / cm -2 Up to 30g / cm -2 , 5g / cm -2 Up to 20g / cm -2 In the range of and including 5g / cm -2 and 50 μg / cm -2 , 5g / cm -2 and 40 μg / cm -2 , 5g / cm-2 and 30 μg / cm -2 , 5g / cm -2 and 20 μg / cm -2 , such as at 8g / cm -2 Up to 15g / cm -2 In the range of and including 8g / cm -2 and 15 μg / cm -2 The catalyst loading of the membrane may be determined by inductively coupled plasma mass spectrometry (ICP-MS).

[0044] The composite catalyst layer has a thickness in the range of 5 μm to 30 μm and including 5 μm and 30 μm. Compared with using a thinner catalyst layer (such as a catalyst layer applied to the membrane surface), the dispersion of particles of the unloaded composite catalyst in the membrane layer of at least 5 μm provides improved membrane stability benefits. The use of a composite catalyst layer having a thickness greater than 30 μm does not need to significantly reduce hydrogen permeation, and may provide manufacturing difficulties, particularly when forming a non-laminated membrane structure. The thickness of the composite catalyst layer can be determined by SEM analysis of the cross section of the membrane. It is preferred that the composite catalyst layer has a thickness in the range of 5 μm to 20 μm and including 5 μm and 20 μm, such as between 7 μm and 15 μm. Such thickness provides a suitable balance between the reduction of hydrogen permeation caused by the formed membrane and manufacturing efficiency.

[0045] The membrane is formed by a method that does not require a lamination step to form the membrane, for example by depositing multiple layers of ion-conducting polymers on top of each other via a liquid deposition process such as printing, spraying or coating.

[0046] The membrane is a single adhered polymer membrane comprising multiple ion-conducting polymer layers. As used herein, the term "adhered" means that the membrane does not contain internal lamination interfaces.

[0047] The lamination of ion-conducting membranes includes squeezing and / or bonding together at least two solid ion-conducting membranes, such membranes are optionally coated with a catalyst layer. A lamination interface is formed between the two membranes, wherein the solid surfaces of the individual membranes are pressed and / or bonded together. The lamination interface includes physical defects. In addition, the structure and / or chemical properties of the lamination interface are also different from those of the main polymer material. This is because when the solid membrane is formed, the outer surface of the solid membrane has surface features different from those in the main material. For example, a hydrophobic surface layer is formed on the membrane surface at the air interface. Raman spectroscopy can detect this difference. Therefore, when two solid membranes are pressed together, the lamination interface formed by the two solid surfaces is different in chemical and / or structural form compared to the main body of the ion-conducting polymer material. Therefore, microscopy and spectroscopy techniques can distinguish between the lamination interface between the ion-conducting polymer layers and the interface formed by a liquid deposition process (such as printing, spraying or coating of layers) to build a multilayer structure. That is, the non-laminated interface is different from the lamination interface in structure and / or chemistry, and is not just a feature of the manufacturing method. In addition, in the absence of a priori knowledge of the manufacturing method, the non-laminated interface can be identified as non-laminated in the film. Examples of analytical techniques for detecting laminated interfaces include cross-sectional SEM. Changes in crystallinity at the interface can be detected using cross-sectional TEM. Other techniques for detecting laminated interfaces include 13C / 1H / 19F solid-state NMR, neutron diffraction and / or a combination of two or more of the above techniques.

[0048] Due to physical defects and / or chemical changes at the lamination interfaces between ion-conducting polymer membranes, such interfaces can increase the resistance of the multilayer ion-conducting membrane. Therefore, it has been found to be advantageous to build the multilayer membrane structure by depositing ion-conducting polymer layers dispersed in a liquid solvent, rather than manufacturing the multilayer ion-conducting membrane via lamination of separate solid layers / films of ion-conducting polymers.

[0049] Preferably, the membrane comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It may be preferred that the composite catalyst layer does not comprise a strengthener polymer.

[0050] The reinforcing agent material may include a porous reinforcing agent polymer sheet impregnated with an ion conducting polymer, the reinforcing agent material being optionally expanded polytetrafluoroethylene (ePTFE). Since typical reinforcing agent polymer materials do not conduct ions, or do not conduct ions sufficiently, a porous reinforcing agent polymer is used to form the reinforcing agent layer, the porous reinforcing agent polymer being impregnated with the ion conducting polymer through the pores of the material to provide an ion conducting path from one side of the layer to the other side of the layer.

[0051] Preferably, the membrane includes a radical reducing additive (e.g., a peroxide radical reducing additive, such as ceria). It should be noted that peroxides can decompose to form a series of free radicals (O, OH, OOH), and the radical reducing additive can reduce the amount of one, multiple, or all of these free radicals. The radical reducing additive can be dispersed in the composite catalyst layer.

[0052] Typically, the membrane is configured so that, with reference Figure 1 , the composite catalyst layer (1) is disposed between the first ion-conducting polymer layer (2) and the second ion-conducting polymer layer (3). In such a configuration, the second face (4) of the first ion-conducting polymer layer (2) and the second face (5) of the second ion-conducting polymer layer (3) each face inwardly toward the composite catalyst layer (1). The first face (6) of the first ion-conducting polymer layer (2) and the first face (7) of the second ion-conducting polymer layer (3) are the outer surfaces of the membrane, i.e., facing the anode and cathode when incorporated into, for example, a water electrolyzer.

[0053] Suitably, the membrane consists of a composite catalyst layer disposed between a first ion conducting polymer layer and a second ion conducting polymer layer. Those skilled in the art will appreciate that the first ion conducting polymer layer and the second ion conducting polymer layer may be formed from one or more sub-layers, which may have the same or different compositions.

[0054] In the case where the membrane is used in a PEM electrochemical device, the ion conducting polymer present in the first ion conducting polymer layer and the second ion conducting polymer layer is suitably a proton conducting polymer, and in particular a partially fluorinated sulfonic acid polymer or a fully fluorinated sulfonic acid polymer. Examples of suitable proton conducting polymers include perfluorosulfonic acid ionomers, such as perfluorosulfonic acid ionomers available from 3M Company or Aquivion (RTM) ion conducting polymers available from Solvay. It is preferred that the ion conducting polymer in the first ion conducting layer and / or the second ion conducting layer is the same as the ion conducting polymer in the composite catalyst layer. It is alternatively preferred that the ion conducting polymer in the first ion conducting layer and / or the second ion conducting layer is different from the ion conducting polymer in the composite catalyst layer.

[0055] Typically, a strengthener polymer and / or a free radical reducing agent (eg, a peroxide radical reducing additive such as ceria) is present in the first ion conducting polymer layer and / or the second ion conducting polymer layer.

[0056] Preferably, the thickness of the first ion conducting polymer layer is less than the thickness of the second ion conducting polymer layer.This asymmetry enables the composite catalyst layer to be placed closer to the anode than the cathode in a water electrolyzer configuration, which is believed to be beneficial in reducing hydrogen permeation.

[0057] Preferably, the first ion-conducting polymer layer has a thickness in the range of 5 μm to 30 μm and including 5 μm and 30 μm, such as in the range of 5 μm to 20 μm and including 5 μm and 20 μm, or 5 μm to 15 μm, or 7 μm to 15 μm. Such thickness of the first ion-conducting polymer layer is considered by the inventors to provide a suitable distance between the anode layer and the composite catalyst in a formed CCM for a water electrolyzer to provide a significant reduction in hydrogen permeation.

[0058] Preferably, the second ion conducting polymer layer has a thickness in the range of 10 to 90 μm and including 10 μm and 90 μm, such as in the range of 20 to 70 μm, 40 to 70 μm or 25 to 45 μm and including 20 μm and 70 μm, 40 to 70 μm or 25 to 45 μm.

[0059] The thickness of the ion-conducting polymer layer can be adjusted, for example, by varying the number of deposition steps of the ion-conducting polymer during the membrane manufacturing process, or by varying the pump speed during the deposition of the ion-conducting polymer.

[0060] Preferably, the membrane comprises or consists of: (i) a first ion conducting layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion conducting layer having a thickness in the range of 25 μm to 45 μm and including 25 μm and 45 μm; and (iii) a composite catalyst layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and disposed between the first ion conducting layer and the second ion conducting layer. In such a configuration, preferably, the second ion conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It has been found that such a membrane structure provides a particularly suitable balance between membrane resistance and hydrogen permeation level.

[0061] It is preferred that the membrane comprises or consists of: (i) a first ion conducting layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion conducting layer having a thickness in the range of 40 μm to 70 μm and including 40 μm and 70 μm; and (iii) a composite catalyst layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and disposed between the first ion conducting layer and the second ion conducting layer. In such a configuration, it is preferred that the second ion conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It is further preferred that the second ion conducting layer comprises two strengthener polymer regions, such as two sublayers comprising a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). Such membrane structures enable operation at particularly high gas pressure differentials across the membrane while maintaining hydrogen permeation and low membrane resistance.

[0062] The membranes as described herein may suitably be used as part of a catalyst coated membrane (CCM).Such CCMs have an anode catalyst layer and / or a cathode catalyst layer applied to the face of the membrane.

[0063] In the case of a CCM for a water electrolyzer, a cathode catalyst layer may be applied to the surface of a membrane comprising a catalyst for catalyzing the hydrogen evolution reaction. Preferably, the cathode catalyst layer comprises platinum, such as a carbon-supported platinum catalyst. The catalyst material may be formulated as an ink, printed onto a PTFE sheet ex situ, and transferred to the membrane by hot pressing. Alternatively, the ink may be applied directly to the membrane.

[0064] It may be preferred that the cathode catalyst layer comprises platinum and has a carbon-supported platinum material (such as a carbon-supported platinum material) of less than 1 mg. Pt cm -2 Surprisingly, it has been found that when using a carbon-supported platinum catalyst material, reducing the platinum loading actually results in an improvement in performance in terms of current density. That is, reducing the platinum loading using a carbon-supported platinum catalyst material surprisingly results in an increase in current density at a given potential. That is, there is also a lower limit to the amount of platinum that must be provided. Therefore, the platinum loading of the cathode layer is suitably greater than 0.01 mg Pt cm -2 , 0.04mg Pt cm -2 or 0.06mg Pt cm -2 .

[0065] The cathode catalyst layer may comprise a carbon-supported platinum catalyst material, which is between 20% and 60% by weight of platinum, optionally between 40% and 60% by weight of platinum. Platinum is advantageously provided as nanoparticles on a carbon support material. The platinum nanoparticles may have a crystallite size of at least 1 nm, 2 nm, or 3 nm; not more than 15 nm, 10 nm, or 6 nm; or within a range defined by any combination of the above lower and upper limits. The crystallite size may be measured by XRD and fitted using Rietveld analysis. Using Cu Kα radiation ( and ) X-ray diffraction data were collected on a Bruker AXSD8. Crystallite sizes were calculated by Rietveld refinement using the LVol-IB method.

[0066] The cathode catalyst layer may comprise a carbon-supported platinum catalyst material, wherein the carbon support material is a partially graphitized carbon material (e.g., heat-treated carbon black). Graphite materials are more corrosion resistant. However, graphite support materials have a low surface area. Therefore, there is a compromise between the requirements of high surface area and high corrosion resistance. It has been found that partially graphitized materials are a good compromise between the surface area requirements and corrosion resistance requirements of the carbon support in this water electrolyzer application.

[0067] Typically, the cathode catalyst layer comprises both a catalyst and an ion-conducting polymer. The ion-conducting polymer in the cathode catalyst layer can be an ionomer, such as a perfluorosulfonic acid (PFSA) polymer, having an equivalent mass of: not more than 880 EW, 850 EW, or 830 EW; not less than 750 EW, 770 EW, or 790 EW; or within the range defined by any combination of the above upper and lower limits. The side chains of the cathode layer ion-conducting polymer typically each include a sulfonate group. The side chains of the cathode layer ion-conducting polymer may have the structure: -CF2-CF2-CF2-CF2-SO3 H An example of such an ionomer is 800EW 3M C4 side chain. The ion conducting polymer of the cathode layer may be the same as or similar to that used in the membrane.

[0068] The cathode catalyst layer may have an ion-conducting polymer / carbon weight ratio in the range between and including 0.6 and 1.0 (note that this is the weight ratio between the ion-conducting polymer and the carbon, platinum is not considered in this calculation). In addition, the cathode catalyst layer may have a thickness in the range of any one of 1 μm to 15 μm, 4 μm to 15 μm, or 8 μm to 15 μm.

[0069] Examples of such cathode layers include the following features:

[0070] - Nominal Pt loading—0.4 mg Pt cm -2

[0071] -Ion Conducting Polymer—Ionomer 800EW 3M C4 Side Chain

[0072] -Ion-conducting polymer / carbon weight ratio—0.8

[0073] -Thickness—about 10μm to 11μm

[0074] - Catalyst is 50 wt% platinum on carbon

[0075] -Carbon is a partially graphitized carbon support material

[0076] In the case of a CCM for a water electrolyser, an anode catalyst layer may be applied to the surface of the membrane comprising a catalyst for catalyzing the oxygen evolution reaction. In the case of a CCM for a PEMWE, it may be preferred that the anode catalyst layer comprises iridium, such as iridium oxide or a mixed oxide of iridium and another metal or metals.

[0077] The anode material may be formulated as an ink, suitably in an ion-conducting polymer, printed ex situ onto a PTFE sheet, and transferred to the membrane by hot pressing. Alternatively, the ink may be coated directly onto the membrane.

[0078] The anode catalyst layer typically comprises both a catalyst and an ion-conducting polymer. Advantageously, the ion-conducting polymer of the anode catalyst layer differs from the ion-conducting polymer in the membrane in that it has one or more of the following: a higher equivalent mass than the membrane ion-conducting polymer; longer side chains than the membrane ion-conducting polymer; and / or different chemical groups in the side chains compared to the membrane ion-conducting polymer. In contrast, the membrane ion-conducting polymer used in the cathode catalyst layer may be the same as or similar to the membrane ion-conducting polymer used in the ionomer membrane.

[0079] The ion-conducting polymer in the anode catalyst layer preferably has the following equivalent mass: not less than 900EW, 950EW, 1000EW or 1050EW; not more than 1300EW, 1200EW or 1150EW; or within the range defined by any combination of the above lower and upper limits. The side chains of the membrane ion-conducting polymers typically each include a sulfonate group. Optionally, in addition to the ether bonds to the main chain, the side chains of the ion-conducting polymer include ether groups. In addition, optionally, the side chains of the ion-conducting polymer include CF3 groups. The side chains of the ion-conducting polymer may have the following structure: -CF2-CF(CF3)-O-CF2-CF2-SO3H. An example of such an ionomer is Nafion D-2021CS. Nafion D-2021CS is a high equivalent mass ionomer having long side chains with sulfonate end groups. In the presence of water, the sulfonate groups hydrate, solvate and dissociate into protons, and this allows protons to be exchanged from the anode to the cathode. In contrast, the ion-conducting polymer in the membrane can be 3M 800, 3M 825 or Asahi 800 ionomers. These ion-conducting polymers have lower equivalent masses and shorter side chains.

[0080] The anode catalyst layer may comprise between 5 wt % and 20 wt %, for example between 8 wt % and 15 wt % of the ion-conducting polymer. Suitably, the amount of catalyst material in the anode catalyst layer may be between 80 wt % and 95 wt %, optionally between 85 wt % and 92 wt %. The iridium loading of the anode catalyst layer is preferably less than 3 mg Ir / cm 2 , optionally at 0.05 mg Ir / cm 2 and 3mg Ir / cm 2 The iridium-containing catalyst material may be an iridium oxide catalyst material, and the anode catalyst layer may have a thickness between 6 μm and 15 μm.

[0081] Typically, the CCM comprises a membrane comprising a first ion conducting polymer layer and a second ion conducting polymer layer, wherein the composite catalyst layer is disposed between the first ion conducting polymer layer and the second ion conducting polymer layer, as described above. Preferably, the CCM is configured such that the composite catalyst layer is closer to the anode catalyst layer than the cathode catalyst layer. It may be further preferred that the thickness of the second ion conducting polymer layer is greater than the thickness of the first ion conducting polymer layer. Such a configuration is proposed to have benefits in reducing hydrogen permeation.

[0082] Suitably, the CCM is configured such that, with reference to Figure 2The second side (4) of the first ion-conducting polymer layer (2) and the second side (5) of the second ion-conducting polymer layer (3) each face inward toward the composite catalyst layer (1). The anode catalyst layer (8) (if present) is disposed on the first side (6) of the first ion-conducting polymer layer (2). The cathode catalyst layer (9) (if present) is disposed on the first side (6) of the second ion-conducting polymer layer (3).

[0083] Preferably, the catalyst coated membrane comprises a membrane comprising or consisting of: (i) a first ion conducting layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion conducting layer having a thickness in the range of 25 μm to 45 μm and including 25 μm and 45 μm; and (iii) a composite catalyst layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and disposed between the first ion conducting layer and the second ion conducting layer, and wherein the second face of the first ion conducting polymer layer and the second face of the second ion conducting polymer layer each face inwardly toward the composite catalyst layer, and wherein the anode catalyst layer as described above is disposed on the first face of the first ion conducting layer and / or the cathode catalyst layer as described above is disposed on the first face of the second ion conducting layer. In such configurations, preferably, the second ion conducting layer comprises a strengthener polymer, such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI).

[0084] Preferably, the catalyst coated membrane comprises a membrane comprising or consisting of: (i) a first ion conducting layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm; (ii) a second ion conducting layer having a thickness in the range of 40 μm to 70 μm and including 40 μm and 70 μm; and (iii) a composite catalyst layer having a thickness in the range of 5 μm to 15 μm and including 5 μm and 15 μm and disposed between the first ion conducting layer and the second ion conducting layer, and wherein the second face of the first ion conducting polymer layer and the second face of the second ion conducting polymer layer each face inwardly toward the composite catalyst layer, and wherein the anode catalyst layer as described above is disposed on the first face of the first ion conducting layer and / or the cathode catalyst layer as described above is disposed on the first face of the second ion conducting layer. In such configurations, preferably, the second ion conducting layer comprises a strengthener polymer such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI). It may further be preferred that the second ion conducting layer comprises two strengthener polymer regions, such as two sub-layers comprising a strengthener polymer such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI).

[0085] A method for manufacturing the electrolyte membrane as described above is also provided, the method comprising the following steps:

[0086] (i) forming an ink comprising particles of an unsupported composite catalyst and an ion-conducting polymer;

[0087] (ii) Producing a composite catalyst layer from the ink.

[0088] Where the particles of the unsupported composite catalyst are platinum particles, it is preferred that the platinum particles are provided in the form of platinum black. It has been found that platinum black can be efficiently processed to provide inks suitable for use in the methods as described herein and exhibits less agglomeration during ink formation than other platinum sources, such as carbon-supported platinum.

[0089] Preferably, the particles of the unsupported composite catalyst in the ink have a d90 of less than 3.0 μm. The particle size distribution can be determined by using a laser diffraction method. For example, the d90 can be determined by diluting the ink with 80:20 (v / v) ethanol:water and analyzing the particle size distribution by laser diffraction, such as by using a Malvern Mastersizer 3000. The term "d90" for particles in the ink refers to the particle size based on volume (the particle diameter value at 90% in the cumulative volume distribution, i.e., 90% by volume of the particles in the sample have a diameter less than this value).

[0090] The desired particle size distribution may suitably be achieved by processing the ink using high shear techniques such as microfluidisation.Preferably, forming the ink in step (i) comprises passing a dispersion of a platinum source (such as platinum black) and an ion-conducting polymer through a microfluidiser.

[0091] The ink typically includes an ion-conducting polymer dispersed in a solvent. The solvent may be a mixture of an organic solvent and water. For example, the solvent may be a mixture of an alcohol (e.g., ethanol or propanol) and water. The volume ratio of the organic solvent (such as ethanol) to water may be: at least 60:40, 70:30, or 75:25; not more than 95:5; 90:10 or 85:15; or within a range defined by any combination of the above lower and upper limits. The solvent is formulated to achieve the desired dispersion, coating, and drying characteristics.

[0092] The ion-conducting polymer may be provided in the ink at the following weight percentages relative to the total weight of the composite catalyst and the ion-conducting polymer: at least 7 weight %, 10 weight %, 14 weight % or 16 weight %; not more than 22 weight %, 20 weight % or 18 weight %; or within the range defined by any combination of the above lower and upper limits. The ion-conducting polymer content is selected to achieve the desired dispersion, coating and drying characteristics.

[0093] The ink may also include a free radical reducing additive (e.g., a peroxide free radical reducing additive such as ceria). For example, the free radical reducing additive may be provided in the dispersion at the following weight percentages relative to the weight of the ion-conducting polymer: at least 0.15 wt%, 0.20 wt%, or 0.23 wt%; not more than 0.35 wt%, 0.30 wt%, or 0.28 wt%; or within the range defined by any combination of the above lower and upper limits.

[0094] The method comprises the step of making a composite catalyst layer from an ink. The composite catalyst layer is typically formed by casting or printing the ink onto a substrate to form a layer. The layer thus formed may be dried or at least partially dried before depositing another ionomer layer thereon.

[0095] Typically, the substrate is an ion conducting polymer layer, such as a first ion conducting polymer layer or a second ion conducting polymer layer. Preferably, step (ii) comprises making the composite catalyst layer from the ink by depositing the ink onto the first ion conducting polymer layer.

[0096] Further ion conducting polymer layers may be deposited to form the membrane.Preferably, the method comprises step (iii) adding a second ion conducting polymer layer such that the composite catalyst layer is disposed between the first ion conducting polymer layer and the second ion conducting polymer layer.

[0097] The membrane can be formed by sequential printing of layers. As an example, the membrane can be formed as follows. In a first process step, an ion-conducting polymer layer is applied to a backing layer. Subsequently, the first ion-conducting polymer layer is dried. In a second process step, an ink containing a composite catalyst is applied to the first ion-conducting polymer layer. Subsequently, the composite catalyst layer is dried. During an additional process step for forming a second ion-conducting polymer layer, the application and drying sequence is continued to produce additional ion-conducting polymer sublayers. A reinforcing agent material can be included in one or more coating processes.

[0098] The membrane structure as described above can be coated with a cathode catalyst and an anode catalyst to form a catalyst coated membrane (CCM) for a water electrolyzer. The specific type of catalyst for the cathode and anode can vary. In addition, the method of deposition can vary. An example of a suitable cathode catalyst for a water electrolyzer is a carbon-supported platinum catalyst, optionally provided in the form of a decal. In the case of a CCM for a PEMWE, an iridium oxide-based catalyst can be used for the anode. The iridium oxide-based catalyst can be prepared into an ink comprising an ion-conducting polymer, 1-propanol and water, and is rod-coated onto a Teflon sheet and dried to form a decal. The catalyst decal can be hot-pressed with the membrane to form a CCM.

[0099] The present invention will now be described with reference to the following examples, which are provided to aid understanding of the present invention and are not intended to limit the scope of the present invention.

[0100] Example

[0101] Example 1 - Formation of ink containing composite catalyst

[0102] A mixture of an ion-conducting polymer (PFSA ionomer, 825EW, 3M Advanced Materials) and ethanol:water (80:20) was prepared. Platinum black catalyst (Johnson Matthey Co., Ltd.) was added to the mixture, with a target amount of 8.8 wt% based on the total weight of platinum, ionomer, ethanol, and water.

[0103] The mixture was passed through a microfluidizer (Microfluidics M-110P) using a z-type chamber at 30,000 psi until the observable viscosity of the ink decreased significantly.

[0104] The particle size distribution of the platinum particles in the ink was analyzed using a Mastersizer 3000, indicating a d90 of about 0.9 μm and a d50 of about 0.17 μm.

[0105] The concentrated ink was then diluted again using a mixture of 3M ionomer PFSA 825EW and ethanol:water (80:20) to achieve 100% water per cm in the formed film. 2 About 10 μg of Pt.

[0106] Example 2 - Formation of a 50 μm proton exchange membrane in combination with a composite catalyst layer

[0107] A 50 μm proton exchange membrane incorporating a composite catalyst layer was prepared using a slot dye coating method using a series of five printing / coating steps on a double decal substrate (PET with one face release layer), using the composite catalyst-containing ink produced according to Example 1 in the second step.

[0108] All other layers were formed from an ink containing perfluorosulfonic acid (PFSA) ionomer (3M 800EW PFSA ionomer), ceria (0.3 wt % relative to the weight of the ionomer) in ethanol:water (80:20). The reinforcement polymer was added to the ink used for process 3 by adding an expanded polytetrafluoroethylene (ePTFE) reinforcement. The following table summarizes the materials and methods used to construct the membrane.

[0109] The five coating steps used to make the 50 μm film are as follows:

[0110]

[0111] The films were dried at temperatures between 100°C and 160°C and subsequently annealed at 160°C.

[0112] Example 3 - Combining a composite catalyst layer and a single region 80 μm proton exchange membrane with ePTFE reinforcement Formation

[0113] The membrane was produced according to Example 2, wherein three additional coating steps were added to form an 80 μm proton exchange membrane.

[0114] Example 4 - Combining a composite catalyst layer and an 80 μm proton exchange membrane with two regions of ePTFE reinforcement Formation

[0115] The membrane was produced according to Example 1 using the following series of 7 steps: :

[0116]

[0117] Membrane analysis and characterization

[0118] Inductively Coupled Plasma Mass Spectrometry (ICP-MS):

[0119] The platinum loading in the 50 μm membrane produced in Example 2 was measured by ICP-MS to be 13 μg / cm 2 (per 1cm 2 Pt mass of the film).

[0120] The platinum loading in the 80 μm membrane produced in Example 3 was measured by ICP-MS to be 13 μg / cm 2 .

[0121] Scanning Electron Microscopy (SEM): A cross section of each membrane after fabrication was embedded in resin, ground, polished and carbon coated for SEM. The samples were analyzed using a Zeiss Ultra 55 field emission electron microscope. The boundary between a composite catalyst layer and another layer was determined by where the dispersion of the composite catalyst ended.

[0122] Figure 3 A SEM image of a cross section of a 50 μm membrane is shown. This shows that the membrane thickness is 50 μm and there are platinum particles dispersed in a composite catalyst layer with a thickness of about 12 μm.

[0123] Analysis of the platinum particle size distribution from SEM images of the 50 film showed a d90 of about 2.5 μm and a d50 of about 1.2 μm.

[0124] Testing of Catalyst Coated Membranes (CCM)

[0125] CCMs were prepared using 50 μm proton exchange membranes and 80 μm proton exchange membranes containing composite catalysts prepared according to the methods of Examples 2 and 3 and equivalent comparative examples produced according to Examples 2 and 3, but without platinum, for Run 2 (i.e., without composite catalysts). A Pt / C cathode catalyst layer (with a Pt loading of 0.37 mg cm -2 Pt) and IrOx anode catalyst layer (with Ir loading of 2 mg cm -2 ) to prepare a CCM. In the case of a CCM incorporating a composite catalyst, the anode layer is applied to the face of the membrane closest to the composite catalyst layer.

[0126] Hydrogen permeation

[0127] The hydrogen permeation level of each CCM was measured at different pressures using the following method:

[0128] A water electrolysis cell incorporating the catalyst coated membrane to be tested was prepared. The cell temperature was maintained at 80°C, and the anode pressure and cathode pressure were set to 2 bar. Next, the current density was set to 2 A / cm 2 The cathode pressure was increased stepwise from 2 bar to 6 bar, 10 bar and 15 bar, with each step lasting a minimum of 45 minutes. The percentage of H2 in oxygen at the anode gas outlet was measured by a compact GC 4.0 gas chromatograph (GC) from Global Analysis Solutions.

[0129] Figure 4The test results of the CCM are shown. These results show that the hydrogen permeation of the membranes produced according to Examples 2 and 3 is significantly reduced, even at high pressure differentials across the membrane. The 80 μm proton exchange membrane formed according to Example 3 provides the best performance at high pressure differentials.

[0130] Electrical properties

[0131] The electrical performance of CCM is tested by the following methods:

[0132] The CCM was first conditioned by potentiostatic stabilization at 2 V and 80 °C for 18 h to 24 h. Subsequently, polarization measurements were performed. The anodic and cathodic pressures were kept equal at 2 bar. The measurements were performed in a V-shape, with a voltage of 3 A / cm2 at 80 °C. 2 Start at 0.1A / cm2 and then return to 3.0A / cm 2 . The step size is 0.1A / cm 2 The measurements going upward (low current to high current) were used for further analysis.

[0133] Figure 5 Test results for an 80 μm proton exchange membrane are shown. The results show that inclusion of a composite catalyst layer as described herein has no adverse effect on the performance of the membrane. The data indicate that the membrane provides a particularly suitable balance between electrical resistance and hydrogen permeation levels for CCM, enabling high pressure operation.

[0134] CCMs incorporating 50 μm membranes with and without a composite catalyst-containing membrane layer (with a Pt loading of 30 μg / cm 2 ). At 0.3A cm -2 The through-plane resistance of the CCM was measured using electronic impedance spectroscopy (EIS) under the conditions of 64 μΩ / cm for the CCM without the composite catalyst membrane layer. 2 Up to 75μΩ / cm 2 The through-plane resistance is 62 μΩ / cm for a CCM without a composite catalyst-containing membrane layer. 2 Up to 69μΩ / cm 2 These results indicate that the composite catalyst can be advantageously introduced into the membranes set forth above without adversely affecting the resistance value.

Claims

1. An electrolyte membrane comprising a composite catalyst layer, the membrane having a thickness less than or equal to 100 μm, and wherein the composite catalyst layer meets the following requirements: (i) the layer comprises particles of an unsupported composite catalyst dispersed in an ion-conducting polymer; (ii) the layer has a thickness in the range of 5 μm to 30 μm, inclusive; And the electrolyte membrane is a single coherent polymer membrane comprising a plurality of ion-conducting polymer layers. 2 . The electrolyte membrane according to claim 1 , wherein the composite catalyst is selected from one or more of platinum, palladium, and alloys or mixed oxides thereof. 3 . The electrolyte membrane according to claim 1 , wherein the particles of the unsupported composite catalyst have a particle size distribution such that d90 is less than or equal to 3.0 μm.

4. The electrolyte membrane according to any one of the preceding claims, wherein particles of the unsupported composite catalyst have an average particle size greater than 0.1 μm, such as in the range of 0.5 μm to 2.0 μm, inclusive.

5. The electrolyte membrane according to any of the preceding claims, wherein the membrane has a thickness in the range of 5 μm to 100 μm inclusive, preferably in the range of 30 μm to 90 μm inclusive.

6. An electrolyte membrane according to any preceding claim, wherein the membrane comprises a reinforcer polymer such as expanded polytetrafluoroethylene (ePTFE) or polybenzimidazole (PBI).

7. The electrolyte membrane according to any one of the preceding claims, comprising a first ion-conducting polymer layer and a second ion-conducting polymer layer, and wherein the composite catalyst layer is provided between the first ion-conducting polymer layer and the second ion-conducting polymer layer.

8. The electrolyte membrane of claim 7, wherein the membrane comprises a strengthener polymer, and wherein the strengthener polymer is present in the first ion-conducting polymer layer and / or the second ion-conducting polymer layer.

9. An electrolyte membrane according to claim 7 or claim 8, wherein the first ion-conducting polymer layer has a thickness in the range of 5 μm to 30 μm and including 5 μm and 30 μm, preferably in the range of 5 μm to 20 μm and including 5 μm and 20 μm or in the range of 5 μm to 15 μm and including 5 μm and 15 μm.

10. The electrolyte membrane according to any one of claims 6 to 9, wherein the second ion-conducting polymer layer has a thickness in the range of 10 μm to 90 μm, preferably in the range of 40 μm to 70 μm and including 40 μm and 70 μm or in the range of 25 μm to 45 μm and including 25 μm and 45 μm.

11. The electrolyte membrane of any one of claims 7 to 10, wherein the second ion conducting layer contains two strengthener polymer regions.

12. The electrolyte membrane of any one of the preceding claims, wherein the composite catalyst layer has a thickness in the range of 5 μm to 15 μm inclusive.

13. A catalyst coated membrane for an electrochemical device such as a water electrolyzer, the catalyst coated membrane comprising the electrolyte membrane according to any one of claims 1 to 12.

14. A catalyst-coated membrane according to claim 13, wherein the electrolyte membrane comprises a first ion-conducting polymer layer and a second ion-conducting polymer layer, wherein the composite catalyst layer is disposed between the first ion-conducting polymer layer and the second ion-conducting polymer layer, and wherein the anode catalyst layer is disposed on a first surface of the first ion-conducting polymer layer, and the second surface of the first ion-conducting polymer layer faces the direction of the composite catalyst layer. 15 . The catalyst coated membrane of claim 14 , wherein the thickness of the first ion conducting layer is smaller than the thickness of the second ion conducting layer.

16. A catalyst-coated membrane according to any one of claims 13 to 15, wherein the electrolyte membrane comprises a first ion-conducting polymer layer and a second ion-conducting polymer layer, wherein the composite catalyst layer is disposed between the first ion-conducting polymer layer and the second ion-conducting polymer layer, and wherein the cathode catalyst layer is disposed on a first surface of the second ion-conducting polymer layer, and a second surface of the second ion-conducting polymer layer faces in the direction of the composite catalyst layer.

17. The catalyst coated membrane according to any one of claims 14 to 16, wherein the first ion conducting polymer layer has a thickness in the range of 5 μm to 30 μm, inclusive, preferably in the range of 5 μm to 20 μm, inclusive.

18. The catalyst coated membrane according to any one of claims 14 to 17, wherein the second ion conducting polymer layer has a thickness in the range of 10 μm to 90 μm inclusive, preferably in the range of 40 μm to 70 μm inclusive.

19. A water electrolyser comprising a membrane according to any one of claims 1 to 12 or a catalyst coated membrane according to any one of claims 13 to 18.

20. A fuel cell comprising a membrane according to any one of claims 1 to 12 or a catalyst coated membrane according to any one of claims 13 to 18.

21. A method for manufacturing an electrolyte membrane according to any one of claims 1 to 12, the method comprising the following steps: (i) forming an ink comprising particles of an unsupported composite catalyst and an ion-conducting polymer; (ii) producing a composite catalyst layer from the ink.

22. The method of claim 21, wherein the ink is formed by passing a dispersion of platinum black and an ion-conducting polymer through a microfluidizer.

23. A method according to any one of claims 21 or 22, wherein step (ii) comprises depositing the ink onto a first ion conducting polymer layer.

24. The method of claim 23, comprising the step (iii) of adding a second ion-conducting polymer layer such that the composite catalyst layer is disposed between the first ion-conducting polymer layer and the second ion-conducting polymer layer.

Citation Information

Patent Citations

  • Catalyst-coated membrane having a laminate structure

    WO2018115821A1

  • membrane

    WO2020148545A1